Follow-up of Hydatidiform Mole by Radioimmunoassay of Human Chorionic Gonadotrophin - Crawford, J. W. (1972)
An improved method for the follow-up of patients delivered of a hydatidiform mole using radioimmunoassay of human chorionic gonadotrophin is employed to ensure adequate sensitivity. Four illustrative case histories are described. Their HCG findings are presented to show that this is the principal basis on which decisions should be made. There are three aspects to the work of the laboratory. The technical work of the assay, the clerical effort of patient follow-up, and the clinical interpretation of results. The laboratory keeps a close check on follow-up (one of its most important functions) and receives specimens direct from patients. Overall control of all three aspects is by a clinician. It has been found useful to organize a special clinic for these patients to be seen. In this region it has been possible for this to be run by the same clinician.